Design, Implementation, and Evaluation of Visual Cue Techniques for Augmented and Virtual Reality - Kelley, Brendan Rober, author; Ortega, Francisco R., advisor; McMahan, Ryan P , advisor; Tornatzky, Cyane, committee member; Arefin, Mohammed S., committee member (Colorado State University. Libraries, 2026)
Visual search is a common, everyday task we engage with. Whether searching for a misplaced pair of keys, scanning for hazards during a drive, or looking for a friend in a crowded room, visual search is at the core of many daily activities. Research into visual search has roots in cognitive psychology, but recently, with the expansion of augmented reality (AR) and virtual reality (VR) there has been a growing interest in visual search from human-computer interaction (HCI) researchers. Both AR and VR afford the use of cues to assist in visual search tasks. This dissertation explores various aspects of visual cue design and implementation with relation to both HCI and cognitive psychology research. This begins with comparative explorations on cue design with a complex visual search task for both AR and VR head mounted displays (HMDs). Then, the effects of cueing a subset of targets in a multi target search are evaluated with respect to working memory limits. Finally, an exploration of adaptive target selection is presented that compares an adaptive algorithm with common target selection techniques. The work presented in this document helps to further visual cue research by evaluating established cues in the context of cognitive psychology, and incorporating knowledge from this discipline into HCI research. This leads to several key considerations for future cue designs and AR/VR HMD implementations.